Time trends and case fatality rate of in-hospital treated pulmonary embolism during 11 years of observation in Northwestern Italy - Dentali, Francesco; Ageno, Walter; Pomero, Fulvio; Fenoglio, Luigi; Squizzato, Alessandro; Bonzini, Matteo (Thrombosis and Haemostasis, 2016)
Pulmonary embolism (PE) is a common disorder with high mortality and morbidity rates. However, population-based information on its incidence and prognosis remains limited. We conducted a large epidemiology study collecting data on hospitalisation for PE (from 2002 to 2012) in a population of about 13 million people in Northwestern Italy. Patients were identified using the ICD-9-CM codes: 415.11, 415.19; gender and age specific incidence rate of PE during the study period were estimated using the resident population for each year of the study. Furthermore, time trends in the in-hospital PE-related mortality and case fatality rate were calculated. Results were adjusted for possible confounders. A total of 60,853 patients (mean age 72.8 years, ± 14.1, 59.6 % females) with PE were included; the overall crude incidence rate for the entire study period was 55.4 and 40.6 events per year per 100,000 inhabitants for women and men, respectively (p < 0.001). However, this difference was completely lost after standardisation for age. The incidence of PE significantly increased in both genders during the study period. In-hospital case fatality rate significantly decreased throughout the study period (p < 0.001) in women (from 15.6 % to 10.2 %) and in men (from 17.6 % to 10.1 %). The observed decrease of the in-hospital case-fatality throughout the study period remained significant also after adjustment for possible confounders. In conclusion, time trends over an 11-year period show an increasing incidence of PE, but a significant reduction in mortality during hospitalisation. Reduction in the case fatality rate remained significant after adjustment for these possible confounders.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Venous thromboembolism; pulmonary embolism; mortality; prognosis